Analysis of the Most Suitable Transfer Pricing Method in Making Corresponding Adjustments - Nur M Ikhwanudin; Ning Rahayu (Publikasi Indonesia, 2025)
The implementation of corresponding adjustments in Indonesia has become a pressing issue amid growing concerns over cross-border tax avoidance and transfer pricing manipulation. Corresponding adjustments are designed to prevent double taxation resulting from primary adjustments made by partner countries in international affiliated transactions. However, their practical application in Indonesia remains limited. This study aims to identify the most appropriate transfer pricing method for conducting corresponding adjustments through qualitative analysis based on a literature review. The findings reveal that transfer pricing methods involving both parties as a single entity in affiliated transactions—specifically, the Comparable Uncontrolled Price (CUP) method, the Cost Plus Method (CPM), and the Profit Split Method (PSM)—are the most suitable. These methods assess prices recorded by both transaction parties, ensuring that the arm’s length principle is tested consistently using a two-sided approach. Furthermore, these methods conduct transaction-by-transaction testing, resulting in higher comparability and greater accuracy in evaluation. The study recommends the application of two-sided methods for corresponding adjustments in Indonesia due to their superior accuracy and comparability, which can strengthen tax compliance and minimize transfer pricing disputes.